MYC- And MIZ1-dependent vesicular transport of double-strand RNA controls immune evasion in pancreatic ductal adenocarcinoma - Krenz, Bastian; Gebhardt-Wolf, Anneli; Ade, Carsten P.; Gaballa, Abdallah; Roehrig, Florian; Vendelova, Emilia; Baluapuri, Apoorva; Eilers, Ursula; Gallant, Peter; D'Artista, Luana; Wiegering, Armin; Gasteiger, Georg; et al. (Cancer Research, 2021)
Deregulated expression of the MYC oncoprotein enables tumor cells to evade immune surveillance, but the mechanisms underlying this surveillance are poorly understood. We show here that endogenous MYC protects pancreatic ductal adenocarcinoma (PDAC) driven by KRASG12D and TP53R172H from eradication by the immune system. Deletion of TANK-binding kinase 1 (TBK1) bypassed the requirement for high MYC expression. TBK1 was active due to the accumulation of double-stranded RNA (dsRNA), which was derived from inverted repetitive elements localized in introns of nuclear genes. Nuclear-derived dsRNA is packaged into extracellular vesicles and subsequently recognized by toll-like receptor 3 (TLR3) to activate TBK1 and downstream MHC class I expression in an autocrine or paracrine manner before being degraded in lysosomes. MYC suppressed loading of dsRNA onto TLR3 and its subsequent degradation via association with MIZ1. Collectively, these findings suggest that MYC and MIZ1 suppress a surveillance pathway that signals perturbances in mRNA processing to the immune system, which facilitates immune evasion in PDAC.
CRIS-Team Scopus Importer:2023-03-23